PENGARUH PROFITABILITAS DAN LEVERAGE PADA PENGHINDARAN PAJAK DENGAN KONEKSI POLITIK SEBAGAI VARIABEL PEMODERASI - Kadek Angelita Armeitya Dwi Anggraini; Naniek Noviari (Transpublika Publisher, 2024)
The study attempts to gather empirical evidence of the influence of profitability and leverage on tax avoidance with the political connections serving as moderating variables. A mining sector business listed on the Indonesian Stock Exchange (IDX) for the 2018–2022 timeframe makes up the research population. Data analysis techniques are purposive sampling as well as samples selected of 22 companies with 110 observations. Moderate Regression Analysis is utilized to regress data with the help of Eviews 10. The research gains profitability and leverage has a positive effect on tax avoidance. Based on the experiments that have been conducted, the research can validate both the positive accounting theory and the agency theory. The practical implications of research can be used as a reference material for governments to enhance regulatory and supervisory capabilities as well as references for researchers for future advanced studies.